William A.H. Allen papers - Allen, William A. H.
Journals (circa 2,100 pages) with photographs, sketches, and illustrations describing Allen's activities while serving on the U.S.S. Cayuga, assigned to blockade duty on the Gulf Coast during the Civil War, and subsequently on ships in the Mediterranean, Indian, and Pacific Oceans, and at stations on the east and west coasts of the United States and Europe. Contains descriptions of Malaya, Singapore, China, Japan, Peru, Lebanon, Syria, Palestine, and Egypt.
Microfilm edition available
Microfilm produced from originals in Manuscript Division.
Naval officer and engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Navy -- Foreign service -- Indian Ocean; United States. -- Navy -- Foreign service -- Mediterranean Region; United States. -- Navy -- Foreign service -- Pacific Area; United States. -- Navy -- Foreign service -- Europe; Africa -- Description and travel; Asia -- Description and travel; China -- Description and travel; Egypt -- Description and travel; Japan -- Description and travel; Lebanon -- Description and travel; Singapore -- Description and travel; Malaya -- Description and travel; Middle East -- Description and travel; Palestine -- Description and travel; Peru -- Description and travel; Syria -- Description and travel; United States -- History -- Civil War, 1861-1865 -- Blockades; United States -- History -- Civil War, 1861-1865 -- Campaigns; Cayuga (Ship); Engineers; Naval officers